Quantitative Optimisation of Drilling for Brownfields Mineral Exploration - Maturana, Francisco Jose (Curtin University, 2022)
This research presents a novel optimisation framework for brownfields exploration drilling. The proposed optimisation methodology has been developed applying geostatistical methods and modern portfolio theory. The use of conditional simulations ensures that geological uncertainty is taken into account, and the application of Markowitz portfolio theory makes drilling funds allocation optimal. The proposed method closes the gap in current research by incorporating the inherent geological uncertainty of an exploration target and mineral economics.